Allocating Pensions to Younger People Towards a Social Insurance against a Short Life - Ponthiere, Gregory (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book takes as a starting point that welfare states in developed societies do not provide systems of social insurance against the risk of an early death. In contrast to the way in which economically developed countries provide ways of insuring citizens against other possibilities, such as unemployment and disease, no such social insurance mechanism exists for early death. It aims to demonstrate that, despite the impossibility to compensate the victims of a short life once they are identified, and despite the impossibility to identify the persons who will be short-lived (when they are still alive), it is nonetheless possible to construct a social insurance against the risk of a short life by means of age-based statistical discrimination favouring all young persons. Combining philosophical literature with economic analysis, the book re-examines the ethical foundations of social insurance, and proposes a major reform of the welfare state: the construction of a social insurance against a short life. It shows how such an insurance system could be constructed by partially 'reversing' existing pension systems, by offering a period of retirement to all young adults before they start their career. Such a 'reversed' pension system would allocate more free time and opportunities to younger members of society before they enter the labour market, and, hence, this system would also improve the lives of the - unidentified - young persons who will turn out to die prematurely. The book discusses the social desirability of this new system, as well as its financial feasibility and societal consequences, examining how pension allowances paid to young adults may be financed by the work of senior workers. As such, this book demonstrates how the universal uncertainty about the duration of life can be reconciled with the idea of social justice. With an accessible and interdisciplinary approach, this book will be of interest to academics working in a range of fields, including economics, public finance, social insurance, the economics of ageing and the welfare state, economic ethics and political philosophy. Gregory Ponthiere is a Professor of Economics and Philosophy at the Université catholique de Louvain, Hoover Chair in Economic and Social Ethics. .
1. Introduction -- 2. The evil of a premature death -- 3. An insurance against a short life -- 4. Reversing retirement systems -- 5. Conclusions: The Welfare State at a crossroad.
Keywords: Finance, Public; Labor economics; Population -- Economic aspects; Medical economics; Public Finance; Public Economics; Labor and Population Economics; Health Economics